A survey of the extent of information technology applications among six medical school libraries in Metro Manila - Tantiongco, Roman Gregorio G. 1964- (1996)
Except for libraries that are members of the DOST-ESEP library network, the study indicated low levels of automation in most of the respondent institutions, particularly with respect to library information systems.
Overall, the study presents an environmental scan of the medical school library and community as well as the information technologies available. This documentation was undertaken as a stock-taking tool intended for the improvement of library information services and facilities, particularly in cognizance of the fast evolving information technologies that relate to medical and health librarianship.
The information technology application with the highest incidence among respondents is remote database access to HERDIN, with a frequency of four (4) respondents (67 percent), followed by CD-ROM applications with three (3) respondents (50 percent) reporting use of the technology.
The survey is an initial attempt to ascertain the levels of library automation among medical school libraries in Metro Manila. Library automation is discussed using the parameters of library information systems, CD-ROM applications, remote database access, networking and Internet connection and access. A brief portion on network planning is also presented at the latter part of the study.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Libraries -- Automation -- Philippines -- Manila Metropolitan Area; Medical libraries -- Philippines -- Manila Metropolitan Area